2017
DOI: 10.1021/acs.est.6b05113
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sand Bed Depth and Medium Age on Escherichia coli and Turbidity Removal in Biosand Filters

Abstract: The main objective of this study was to build several full-scale biosand filters (BSFs) and assess the long-term (9 month) efficacy for particulate and Escherichia coli removal under simulated real-world usage. Four replicates of three different filter designs were built: the traditional concrete BSF and two scaled-down versions that use a 5 or 2 gal bucket as the casing material. The smaller sand bed depths in the bucket-sized filters did not impact filter performance with respect to (i) turbidity and E. coli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
1
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 16 publications
1
16
1
4
Order By: Relevance
“…Relative low turbidity in ARSFs as compared to SF or SFI can be attributed to the enhanced particle staining due to biolayer formation and change in the media particle/surface. Like the current study, Napotnik et al (2017) too found a positive correlation between turbidity and coliform (E.coli) removal in the long term operated biosand filter. WHO recommends turbidity of < 1 NTU for efficient chlorination (WHO, 2004).…”
Section: Routine Sample Analysis After Biofilm Formationsupporting
confidence: 81%
“…Relative low turbidity in ARSFs as compared to SF or SFI can be attributed to the enhanced particle staining due to biolayer formation and change in the media particle/surface. Like the current study, Napotnik et al (2017) too found a positive correlation between turbidity and coliform (E.coli) removal in the long term operated biosand filter. WHO recommends turbidity of < 1 NTU for efficient chlorination (WHO, 2004).…”
Section: Routine Sample Analysis After Biofilm Formationsupporting
confidence: 81%
“…A filter ripening period after cleaning must be carefully evaluated since the development of the biological layer is essential to improve microorganisms and turbidity removals in HSSFs (Ahammed and Davra, 2011;Bellamy et al, 1985;Napotnik et al, 2017).…”
Section: Day Of Operationmentioning
confidence: 99%
“…Recently, HSSFs have been optimised by using new materials, sand bed depth reduction, different sand sizes and filter ripening ways, adding non-woven blankets to the top layer and operation in continuous and intermittent flows (Calixto et al, 2020;Elliott et al, 2008;Faria Maciel and Sabogal-Paz, 2018;Napotnik et al, 2017;Souza Freitas and Sabogal-Paz, 2019;Young-Rojanschi and Madramootoo, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…realistic source waters (7)(8)(9)(10), most studies have focused on the removal of specific pathogens (11,12) or indicator species (13)(14)(15)(16) with pure cultures added at concentrations many orders of magnitude above what might be encountered during typical operation (5,7,11,12). These studies have led to the identification of several important removal mechanisms for individual microorganisms, including physical filtration (17,18), predation by protozoa (13,19,20), and lysis induced by viruses or reactive oxygen species (13).…”
mentioning
confidence: 99%
“…While filter performance has been shown to improve over time after start-up (9,14), most operational guidelines are driven by empirical observations (30), and the factors that impact microbial succession in these filters have not been well-studied. High variability between filter replicates and overall low levels of replication have also limited the conclusions that can be drawn from previous studies (15,28,31). In a study of two full-scale sand filters, Haig et al found that improvements in the performance of continuously operated filters over time correlated with increases in community evenness and the relative abundance of particular genera (including Sphingobium, Acinetobacter, and Halomonas) (9).…”
mentioning
confidence: 99%